Mechanism of Zn alleviates Cd toxicity in mangrove plants (Kandelia obovata) - Chen, Shan (Frontiers in Plant Science, 2023)
Cadmium (Cd) pollution is very common and serious in mangrove ecosystems in China. Zinc (Zn) has been used to reduce Cd accumulation in plants, and phenolic acid metabolism plays an important role in plant response to stress. In present study, in order to clarify whether Zn alleviates Cd toxicity in mangrove plants through phenolic acid metabolism, the Cd-contaminated Kandelia obovata plants were treated with different concentrations of (0, 80,300, and 400 mg·kg–1) ZnSO4 in a set of pot experiments and the biomass, the contents of Cd, Zn, soluble sugar, chlorophyll and the activities of 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric-reducing antioxidant power (FRAP), l-phenylalanine ammonia-lyase (PAL), shikimic acid dehydrogenase (SKDH), cinnamyl alcohol dehydrogenase (CAD) and polyphenol oxidase (PPO) in the leaves were analyzed. The results showed that Cd contents in the leaves of Kandelia obovata ranged from 0.077 to 0.197 mg·kg–1 under different treatments, and Zn contents ranged from 90.260 to 114.447 mg·kg–1. Low-dose ZnSO4 treatment (80 mg·kg–1) performed significant positive effects on the biomass, phenolic acid metabolism-related enzyme activities, antioxidant capacity, and chlorophyll and soluble sugar contents in the leaves of Cd-contaminated mangrove plants. At the meantime, the addition of low-dose ZnSO4 promoted the biosynthesis of hydroxycinnamic acid, hydroxybenzoic acid, and enhanced the plant antioxidant capacity, thus alleviated Cd toxicity in mangrove plants.